Strategy: planning for competitive edge 2 - May, Gary (Henry Stewart Talks, 2011)
Basic strategic positions, Characteristics of strategic positions, Focused differentiation, Tactics & execution, Creating & tracking action plans, Measuring success, Financial and customer perspectives, Internal processes, Learning and growth, How strategic leaders spend their time, Communicating vision-mission-strategy, Selecting and developing your team, Promoting integrity and ethical behavior, Building a culture of innovation, Managing the resource portfolio, Advanced concepts in the strategic process, Bottom line on strategy